Clinical Profile of Low Vision in Children - Gupta, Jewwl D; Bhattarai, Sanjeev; Sharma, Anand K; Joshi, Niraj D; Gautam, Pragati; Chhetriq, Suraj (Journal of Institute of Medicine Nepal, 2021)
Introduction: Visual impairment in children is more common in developing countries like Nepal. A low vision service has been found to be effective in significantly improving their overall development and quality of life. The main aim of this study was to determine the causes of low vision in pediatric population along with their refractive error distribution and visual functions. Methods: A descriptive cross sectional study was carried out in Tribhuvan University, BP Koirala Lions Center for Ophthalmic Studies. A total of 50 low vision children were under went detail low vision examination. They were selected through purposive sampling. Data was analyzed by using the descriptive and inferential statistics with SPSS version 19.0. Results: The study findings showed, most common cause of visual impairment in low vision children was refractive error (20%), followed by congenital cataract (18%) and macular dystrophy (16%). The most commonly prescribed low vision device for distance was telescope and for near was spectacle magnifier. There was average acuity improvement of five lines in distance visual acuity with low vision devices. Conclusion: The study concluded that refractive error and congenital cataract being the commonest cause of low vision in children, which reflect poor accessibility of care service among Nepalese children. Refractive error, the major cause of visual impairment could have been managed even in primary eye care center in Nepal. Children with impairment have potential visual acuity that can be improved with low vision services.